KI AGENG SURYOMENTARAM: KAWRUH JIWA CONSTRUCTION - Safei, Abdullah (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
For decades, Indonesia’s development has placed more emphasis on physical aspects. Social sciences were abandoned because the government only looked for easy things. Society will surrender when all that is done is physical development, but social science is not developed. Even only given a small portion. In a national context, society needs to have an independent spirit. The government needs to build the soul of citizens by developing and changing the soul of the colonized into an independent soul. Many events that occur in society are caused by humans starting not to understand their true nature. Forgot to fix a pure soul. As a result, humans carry out actions that are not by religious rules or norms. This research is qualitative with a philosophy-praxis-sufism perspective and it can be concluded that Ki Ageng Suryomentaram in his thoughts as outlined in the book “Ilmu Kawruh Jiwa Suryomentaram, History and the Path to Happiness” emphasizes that he invites us as Indonesian people to feel the taste of life, examine every feeling, and reach the true meaning of happiness. True happiness is not out there but within yourself. Free and independent happiness does not depend on time, place, and circumstances. Understanding the soul will make humans understand their nature in life and society. When humans become aware and begin to understand or understand the soul, they will be able to improve themselves, maintain their actions and attitudes, and understand other people.